Facility design and management handbook - Teicholz, Eric. (New York : McGraw-Hill, 2001)
The practice of facility design and management has changed dramatically over the years. This Handbook covers the business needs, practices, and technology infrastructure of various aspects of facility planning, design, and management.
Facility management: an introduction / Timothy Springer --
Benchmarking / Edmond P. Rondeau --
Strategic planning / Loree Goffigon --
Business transformation and facility management / Alex K. Lam --
Financial management for facility managers / Fred Klammt --
Ultimate customer service / Stormy Friday --
Disaster recovery planning / L. David McDaniel --
Alternative workplaces / Jeff Austin ... [et al.] --
Facilities condition assessment / Harvey H. Kaiser, Thomas Davies --
Thinking globally: the competitive edge / Dru Meadows --
Sustainable design / David Lehrer --
Smart buildings, intelligent buildings / Vivian Loftness ... [et al.] --
Lighting / Gary Steffy --
Ergonomics and workplaces / Timothy Springer --
Managing the new healthcare real estate portfolio: a case study / Tom DeChant, John Messervy, Meredith Spear --
Organizational readiness case study: implementing technology at Rocketdyne, a Boeing company / Carolyn Castillo --
Project management and integration / Stephen R. Hagan --
Real estate portfolio management / Stephen Bell --
Supporting the mission of the organization: an approach to portfolio management / Francoise Szigeti, Gerald Davis --
The design and construction process / John D. Macomber --
Space and asset management / Bill Tracy --
Operations and maintenance / Graham Lane Thomas --
Energy management / Al Ferreira --
Security / Roy Spillenkothen, Ron Massa --
Overview and current state of FM technology / Eric Teicholz --
Integrating the Internet into FM / Bruce Cox --
A/E/C industry case study: the birth and development of a collaborative extranet, Bidcom / Charlie Kuffner --
Technology at the architect of the capitol: a case study / Jim Barlow, James White --
Michigan State University facility management master's level certificate program: a case study / Carroll Thatcher ... [et al.] --
GIS case study: space management at the University of Minnesota / David A. Jordani, Debra Gondeck-Becker --
Teaching technology at the University of New South Wales: a case study / Alan White.
Includes bibliographical references and index.
ARC
Department of Architecture
Keywords: Facility management; Factories -- Design and construction; Production planning